Studi Ḥadīṡ Tentang Larangan Mencabut Uban Dengan Pendekatan Ilmu Kesehatan (Kajian Takhri Al- Ḥadīṡ) - Amir, Sulaiman Muhammad; Munandar, Munandar; Nazmi, Khairin (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
Gray hair is no longer a taboo, many parents and even teenagers have gray hair. This is due to several factors. Some are due to age, pigment and hormone factors and other causes. The presence of visible gray hair makes people uncomfortable and feel less confident. Therefore, many people choose to pluck the gray hair on their heads. Whereas in several Ḥadīths of the Apostle it is said that gray hair is a noble thing when it grows on a person's head, and it will be a light for him on the Day of Judgment. The type of research used in this study is library research. Where data collection is obtained from examining books related to this discussion, then analyzed using the takhrij method, sanad criticism and matan criticism and using the ma'ani al-Ḥadīth approach to the meaning of the Ḥadīth. Based on the research conducted by the author, it is found that the Sanad and Matan of this Hadīth are recognized as Hasan, so it can be used as an evidence, so it can be determined that the matan of the Hadīth narrated by Abu Dawud above is Hasan because there is no shuzuz and illat in the matan of the Hadīth. Based on the medical perspective, it is also recommended not to pluck gray hair because it can cause several harmful effects including increasing the risk of infection and scarring, ingrown hair, changes in hair texture, impaired hair growth, hair loss, thinning hair to baldness and folliculitis